2018
DOI: 10.1590/s1678-9946201860076
|View full text |Cite
|
Sign up to set email alerts
|

A survey of freshwater and terrestrial snails in a predominantly urban municipality of Rio de Janeiro State, Brazil, with emphasis on human parasites vectors

Abstract: Many snail species act as intermediate hosts of helminths that transmit diseases to humans and animals, such as schistosomiasis and angiostrongyliasis. São Gonçalo, a mostly urban municipality in Rio de Janeiro State, Brazil, has undergone fundamental environmental impacts, which favor the establishment of a range of diseases, for which snails act as the intermediate hosts of the etiological agents. In the present study, freshwater and terrestrial snail populations were surveyed in different environments withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Angiostrongylus cantonensis has also been found in association with A. fulica on islands, such as the Hawaiian archipelago (Kim et al, 2014) and French Polynesia, in the Pacific Ocean (Fontanilla & Wade, 2012), Mayotte Island, in the Indian Ocean (Epelboin et al, 2016) and the Ilha Grande in Brazil (Oliveira & Santos, 2018), in the Atlantic Ocean. This nematode has also been recorded in Ecuador (Solórzano-Alava et al, 2019), Cuba (Meijides-Mejías & Robledo, 2019), Colombia (Giraldo et al, 2019), the contiguous United States, in Florida (Kwon et al, 2013;Rollins et al, 2021), Thailand (Dumidae et al, 2019;Jakkul et al, 2021), China (Lv et al, 2009), Japan (Matayoshi et al, 1987;Noda et al, 1987), Malaysia (Lim & Heyneman, 1965) and the Philippines (Tujan et al, 2016). In Europe, the single record from Italy was obtained from a study of snails being raised as pets, which evaluated the potential for the transmission of parasites from the animals to humans, and found snails infected with Rhabditis sp.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Angiostrongylus cantonensis has also been found in association with A. fulica on islands, such as the Hawaiian archipelago (Kim et al, 2014) and French Polynesia, in the Pacific Ocean (Fontanilla & Wade, 2012), Mayotte Island, in the Indian Ocean (Epelboin et al, 2016) and the Ilha Grande in Brazil (Oliveira & Santos, 2018), in the Atlantic Ocean. This nematode has also been recorded in Ecuador (Solórzano-Alava et al, 2019), Cuba (Meijides-Mejías & Robledo, 2019), Colombia (Giraldo et al, 2019), the contiguous United States, in Florida (Kwon et al, 2013;Rollins et al, 2021), Thailand (Dumidae et al, 2019;Jakkul et al, 2021), China (Lv et al, 2009), Japan (Matayoshi et al, 1987;Noda et al, 1987), Malaysia (Lim & Heyneman, 1965) and the Philippines (Tujan et al, 2016). In Europe, the single record from Italy was obtained from a study of snails being raised as pets, which evaluated the potential for the transmission of parasites from the animals to humans, and found snails infected with Rhabditis sp.…”
Section: Discussionmentioning
confidence: 81%
“…In a majority of the studies (50 papers), the nematodes were identified based on the analysis of their external morphology (table 1), with 13 of these studies employing experimental infection (Lim & Heyneman, 1965; Thiengo et al, 2010; Oliveira et al , 2015; Tomaz et al , 2018) and three, morphometry (Maldonado et al , 2010; Smith et al , 2015; Guerino et al , 2017). Molecular methods (polymerase chain reaction (PCR) and the sequencing of molecular markers) were also used ( n = 29 papers), in particular in Brazil (Caldeira et al , 2007; Thiengo et al , 2010; Carvalho et al , 2012; Guerino et al , 2017; Orico et al , 2019; Barbosa et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, malacologic surveys appeared essential in understanding the prevalence of disease-relevant snail species, their infection levels, and changes in their distribution, with many of these studies having been carried out in Brazil [ 7 , 64 ]. The authors mentioned, for example, the disturbance and degradation of natural areas neighboring residential zones as responsible for the proliferation of molluscs.…”
Section: Resultsmentioning
confidence: 99%